Kidney function decline in heart failure patients: an audit of out-patient heart failure services. (29th July 2021) - Lehane, M; Connolly, S; Crowley, M; Hart, C; O"flynn, AM
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: A bidirectional relationship exists between the kidney and the heart; the lower the eGFR the more challenging it is to manage the heart failure (HF) patient. Worsening renal function is common in HF patients and associated with a two-fold increase in mortality and a lower likelihood of being prescribed efficacious HF therapy. The role of cardio-renal interactions in HF is essential to identify risk and subsequent treatment strategies. Purpose: The purpose of this audit is to provide insights into the assessment of renal function in a real world heart failure population by identifying the degree of renal dysfunction and changes in renal function over a five year time frame. Methods: A retrospective audit included patients with HFrEF attending a heart failure service. These patients were classified using KIDGO criteria CKD 1-5. A current eGFR sample was compared with a sample taken five years earlier, identified using the electronic laboratory record. Ethical approval was granted from the Research Ethics Committee. Resultss: 100 patients with HFrEF attending a heart failure service fulfilled the selection criteria of which sixty three patients with an eGFR >60ml/min/1.73 m2 were audited. Of this group 43 were CKD class 2 and 20 were CKD class 1. Thirty seven patients had an eGFR <60ml/min/1.73 m2 of which 9 were class 3b, 9 were CKD class 4 and 1 was CKD Class 5. Of the 100 patients enrolled, 6 were excluded from the analysis of kidney function decline as an eGFR from five years earlier was unavailable. Within a five year time span, 44 patients did not change their CKD class, 31 patients declined by one class, 9 patients declined by two classes, 3 patients declined by three classes and 7 patients improved their kidney function. GFR < 60mL/min/1.73m2, n = 37 GFR > 60mL/min/1.73m2, n = 63 Age – mean (range) 77.8 (49-94) 66.5 (45-89) Gender – female (%) 12 (32%) 16 (25%) Average renal function measurements (mean, range) 6.4 6.7 Total albumin: creatinine ratio measurements 8 6 Actively attending renal service 6 0 Conclusion: Nurses should be aware of the increasing risk conferred by the dual diagnosis of heart failure and chronic kidney disease. Patients with heart failure who have decreasing eGFR levels (especially less than 30 mL/min), should have collaborative management with nephrology services to optimise outcomes. Recognition of CKD in our institution and referral to nephrology services was suboptimal and further work is necessary to optimise the management of these patients.